(untitled) (Biocenosis, 2015)
Environmental Education should be seen as a tool to address environmental goals by boosting the new generation’s awareness of the challenges of environmental care. This study presents the results of a program for children on the consequences of wild mammal roadkills in the area of Sarapiquí. The program was held in six schools: Corazon de Jesus, La Virgen, La Guaria, Chilamate, El Tigre and Horquetas, for 146 children in four and five grades, whose ages ranged from 9 to 10 years. It consisted of 14 activities intended to acquaint students with the general characteristics of wild mammals, as well as the major threats they face, emphasizing road death due to vehicles.